O30-4 Occupational noise exposure during pregnancy and preeclampsia. (1st September 2016) - Selander, Jenny; Albin, Maria; Rylander, Lars; Lewne, Marie; Rosenhall, Ulf; Gustavsson, Per
Abstract : Background: Women of childbearing age are in many parts of the world occupationally active. This leads to a large number of pregnancies potentially exposed to occupational exposures. Occupational and residential noise has been identified as a risk factor for cardiovascular disease in adults. However, very few studies have addressed the association between noise during pregnancy and pregnancy related outcomes such as preeclampsia. Aim: The aim of this study was to investigate if occupational exposure to noise during pregnancy is associated with an increased risk of preeclampsia. Method: This population based cohort study included 667, 642 single births in Sweden 1997–2008. Data on mothers' occupation, smoking habits, age, ethnicity, BMI, leave of absence and socio-economic factors were obtained from the medical birth register, holding data on interviews performed at prenatal care units at 10 weeks of gestation, and from national registers. Occupational noise exposure was classified by a job-exposure-matrix as <75, 75–84, or ≥85 dBLAeq, 8h. Diagnosed cases of preeclampsia were identified from the medical birth register. Results: Preliminary results restricted to full-time working mothers with less than 20 days (median) leave of absence showed an association between maternal occupational noise exposure and preeclampsia, 75–84 dBA adjusted OR 1.08 (95% CI: 1.01, 1.15) and ≥85 dBA adjusted OR 1.45 (95% CI: 1.03, 2.04) vs <75 dBA. Conclusions: These results indicate that occupational noise exposure might be a novel risk factor for preeclampsia. However, the relation to other occupational exposures needs to be evaluated.